The magician's nephew - Lewis, C. S. (Clive Staples) 1898-1963.; Baynes, Pauline (New York Scholastic, 1995)
When Digory and Polly try to return the wicked witch Jadis to her own world, the magic gets mixed up and they all land in Narnia where they witness Aslan blessing the animals with human speech.
Keywords: Fantasy